2022
DOI: 10.1111/pbi.13807
|View full text |Cite
|
Sign up to set email alerts
|

Transposable element insertion: a hidden major source of domesticated phenotypic variation in Brassica rapa

Abstract: Transposable element (TE) is prevalent in plant genomes. However, studies on their impact on phenotypic evolution in crop plants are relatively rare, because systematically identifying TE insertions within a species has been a challenge. Here, we present a novel approach for uncovering TE insertion polymorphisms (TIPs) using pan-genome analysis combined with population-scale resequencing, and we adopt this pipeline to retrieve TIPs in a Brassica rapa germplasm collection. We found that 23% of genes within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 68 publications
(100 reference statements)
3
36
0
Order By: Relevance
“…The genealogical relationships within B. oleracea were consistent with morphotypes rather than geographical origin. The B. rapa lineage in our analysis largely corroborated the one revealed by Cai et al (Cai et al, 2022b) with minor differences, both of which revealed five monophyletic groups for these diverse B. rapa morphotypes. Estimation of divergence times based on Bayesian inference using MCMCTree program suggested that intraspecific diversification for the sister species B. oleracea (~4.21 Mya) and B. rapa (~4.33 Mya) happened simultaneously and shortly after their speciation (~6.5 Mya) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The genealogical relationships within B. oleracea were consistent with morphotypes rather than geographical origin. The B. rapa lineage in our analysis largely corroborated the one revealed by Cai et al (Cai et al, 2022b) with minor differences, both of which revealed five monophyletic groups for these diverse B. rapa morphotypes. Estimation of divergence times based on Bayesian inference using MCMCTree program suggested that intraspecific diversification for the sister species B. oleracea (~4.21 Mya) and B. rapa (~4.33 Mya) happened simultaneously and shortly after their speciation (~6.5 Mya) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The genotypes of 63 Spinacia accessions based on TIPs on the sex chromosomes was determined, as described by Cai et al (2022) [ 31 ]. One sample (PI604780) was removed because of the high missing rate.…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the genotypes of each Spinacia accession as described by Cai et al (2022) [ 31 ]. Specifically, we first defined each TE insertion sequence and their 1 kb upstream and downstream as the TE reference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, β-carotene-derived retinoid plays important roles in circadian clock oscillation, neurogenesis, and vasculature development in animal cells. Recent studies found that retinol also mediates circadian clock oscillations and regulates the development of plant lateral roots in plant cells [ 162 ].…”
Section: Rootstock Genetic and Molecular Regulationmentioning
confidence: 99%